Nitrogen Mineralisation in Vineyard Soils of the Western Cape as Affected by Soil Management Practices - Raath, P.J.; Saayman, D. (South African Journal of Enology and Viticulture, 2017)
Soil management practices like ridging, liming and irrigation are expected to affect the ability of microorganisms to mineralise plant residues in the soil through their effects on water regime, temperature, pH, organic C and total N contents. Investigations into seasonal changes in the mineral N contents of typical vineyard soils, as affected by these practices, were initiated during 1991 in existing vineyard trials. Soil water, soil temperature and mineral N were measured at regular intervals over two growing seasons. Ridged soil showed higher N release than non-ridged soil during winter, resulting in higher mineral N content at budburst. The effect of liming on microbial activity probably abated after 5 years because no difference in mineral N contents were obtained between soils of different pH. Irrigation showed no effect on N release, probably because of treatment design. Decreases in mineral N content during the growing season in soils from all the trials could not always be attributed to uptake by grapevines or to decreases in potentially mineralisable N contents and microbial activity.